Wildfire recovery as a "hot moment" for creating fire-adapted communities. (January 2020) - Schumann, Ronald L.; Mockrin, Miranda; Syphard, Alexandra D.; Whittaker, Joshua; Price, Owen; Gaither, Cassandra Johnson; Emrich, Christopher T.; Butsic, Van
Abstract: Recent decades have witnessed an escalation in the social, economic, and ecological impacts of wildfires worldwide. Wildfire losses stem from the complex interplay of social and ecological forces at multiple scales, including global climate change, regional wildfire regimes altered by human activities, and locally managed wildland-urban interface (WUI) zones where homes increasingly encroach upon wildland vegetation. The coupled nature of the human-ecological system is precisely what makes reducing wildfire risks challenging. As losses from wildfire have accelerated, an emerging research and management objective has been to create fire-adapted communities where ecologically functional levels of wildfire are preserved but risks to human lives and property are minimized. Realizing such a vision will require widespread and decentralized action, but questions remain as to when and how such a transformation could take place. We suggest that the period following a destructive wildfire may provide a "hot moment" for community adaptation. Drawing from literature on natural hazard vulnerability, disaster recovery, and wildfire ecology, this paper proposes a linked social-ecological model of community recovery and adaptation after disaster. The model contends that changes during post-wildfire recovery shape a community's vulnerability to the next wildfire event. While other studies have highlighted linked social-ecological dynamics that influence pre-fire vulnerability, few studies have explored social-ecological feedbacks in post-fire recovery. This model contributes to interdisciplinary social science research on wildfires and to scholarship on community recovery by integrating hazard vulnerability reduction with recovery in a cyclical framework. Furthermore, it is adaptable to a variety of hazards beyond wildfire. The model provides a basis for future empirical work examining the nature and effectiveness of recovery efforts aimed at long-term vulnerability reduction. Highlights: Introduces linked social-ecological model for community recovery from wildfire. Combines recovery and long-term vulnerability reduction in a cyclical framework. Summarizes post-fire social and ecological outcomes of recovery over time. Discusses trade-offs in actualizing the vision of a fire-adapted community. Model is adaptable to an all-hazards environment.